The Function Of Ideology In Translation: A Case Study Of Selected Aljazeera News Headlines Translated Into Arabic - Nabil Al-Awawdeh (Ijaz Arabi Journal of Arabic Learning, 2022)
The translation is an essential aspect of communication between speakers from different linguistic backgrounds. The main job is to render an original text from a source text (ST) into a target text (TT), with an unalloyed commitment to maintain the source language message and meaning and avoid fidelity erosion. In the light of this, every translator has an internally structured ideological disposition which usually comes into play in translation. This study takes a look at the extent to which ideology impacts translation. The study examined the function of ideology in translation. It was implemented through news headlines from Aljazeera-Egypt, translated from English into Arabic. The choice of the news headlines is based on the communicative role of headlines in representing the real news and the extent to which translators usually input their ideologies and ideologies of news organizations involved in translating headlines. The study adopted a simple descriptive approach, and data were analyzed using the Van Dijk approach to the discourse analysis. Findings were made in the study. One significant discovery is the use of deletion and addition process by the news headline translators to alter the meaning and ideology of the main text in the course of shifting to the ideology of the translated text. The alteration could be maximal, partial, or minimal, affecting lexical words, grammatical words, or phrases. Meaning is usually changed, and ideological change is usually apparent. Ideology highlights a notable function in translation, especially when the translator is subjected to function according to the dictates of an organization, such as Aljazeera News.